Yoga versus classical dance therapy to reduce stress in women working from home - Sadawarte, Sneha S.; Sahasrabuddhe, Priya N. (International Journal Of Community Medicine And Public Health, 2022)
Background: COVID-19 pandemic led to rise of work from home job pattern. Although, now the situation is better still the hybrid pattern of work continues. This situation has led to rise in stress levels in women working from home. Early intervention to reduce the stress will help to overcome ill effects of stress like headache, sleep disturbances, mental health issues, hypertension etc. This study aims to understand which intervention works the best to reduce stress in women working from home. Methods: Yoga as an intervention which had sustained posture and breathing control techniques while classical dance therapy-Bharatnatyam had structured basic dance movements and portraying of nine emotions. Pre and post intervention stress values were assessed through an outcome measure-the perceived stress scale-10. Online intervention for thrice a week for four weeks was incorporated. Results: The results interpreted that post four week of intervention through online mode yoga therapy gives statistically and clinically significant decrease in stress levels while classical dance therapy gives clinically significant result but fails to give statistically significant result. Conclusions: Women working from home mostly had moderate stress on perceived stress scale 10. Yoga therapy reduced the stress post four weeks in women working from home. The reduction in stress was statistically significant. Classical dance therapy reduced the stress post four weeks in women working from home. But, the reduction in stress was not statistically significant. Yoga is better than classical dance to reduce stress in women working from home.